TWO NEW SPECIES OF BEGONIA (BEGONIACEAE) FROM SULAWESI, INDONESIA - Ardi, W. H.; Ardaka, I Made; Hartutiningsih, M. Siregar; Lugrayasa, I Nyoman; Thomas, D. C. (Edinburgh Journal of Botany, 2014)
Two new species of Begonia (Begoniaceae), Begonia gambutensis Ardi & D.C.Thomas and Begonia siregarii Ardi & D.C.Thomas, are described from material collected on the Indonesian island of Sulawesi. Both species belong to Begonia section Petermannia. A key to the species in the provinces North Sulawesi and Gorontalo is provided.